1984
DOI: 10.1515/ijsl.1984.47.105
|View full text |Cite
|
Sign up to set email alerts
|

Use of languages and code switching in groups of youths in a barri of Barcelona: communicative norms in spontaneous speech

Abstract: The use of Catalan and Castilian, and of code switching between these two languages, is observed and analyzed in the conversations of youth groups in the Barcelona barri of Sant Andren. The authors try to demonstrate that the institutionalized diglossic situation in Barcelona affects the individual use of Catalan and Castilian even in situations where one language or another is not normatively required. Special attention is devoted to the analysis of the different types of code switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Beebe (1981) and Khati (1987) found that the most important factor in code switching was the identity and status of the listener. This is confirmed in a Spanish study by Calsamiglia and Tuson (1984) which found that when speakers of two dialects conversed, the speakers of the lower status language were more likely to switch than the speakers of the high-status language. Where the relative status of the two speakers is unknown, Scotton (1983) observed that the choice of code was made by a process of negotiation.…”
Section: Theoretical Backgroundsupporting
confidence: 55%
“…Beebe (1981) and Khati (1987) found that the most important factor in code switching was the identity and status of the listener. This is confirmed in a Spanish study by Calsamiglia and Tuson (1984) which found that when speakers of two dialects conversed, the speakers of the lower status language were more likely to switch than the speakers of the high-status language. Where the relative status of the two speakers is unknown, Scotton (1983) observed that the choice of code was made by a process of negotiation.…”
Section: Theoretical Backgroundsupporting
confidence: 55%
“…However, a small advantage is observed in Spanish proficiency, which is likely because exposure to Spanish occurred earlier than to Catalan in this sample. Although previous early studies of Spanish–Catalan code switching in the Barcelona region have shown that language mixing is not frequent (most likely for political reasons, see Calsamiglia and Tuson, 1984 ; Woolard, 1988 ), this tendency might have changed recently because of the efforts of the Catalan autonomic government to increase the presence of Catalan in the schools and media after 1975 (i.e., with the end of the dictatorship period).…”
Section: Methodsmentioning
confidence: 98%
“…In addition, the similarity of the two languages spoken in a community could be reflected in the degree of switching (Odlin, 1989 ; Marian, 2009 ). For example, Catalan–Spanish languages are highly similar Romance languages, sharing a large number of cognate words with similar forms and meanings [“vender” (Spanish) – “vendre” (Catalan), to sell], and switching is commonly observed in many situations (Rodriguez-Fornells et al, 2006 ; see also Calsamiglia and Tuson, 1984 ; Woolard, 1988 ). Interestingly, early observations of naturalistic conversations have suggested that cognate words could act as a language switching trigger.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the specific goals of the study and based on previous experiences (Arias and Anguera, 2004, 2005), the observation instrument was redesigned to include 15 forms of communication. These forms, or dimensions of communication, were derived from the work of Torras de Beà (2013) on group psychotherapy and of Tusón (1995) and Calsamiglia and Tusón (1999) on conversation analysis.…”
Section: Methodsmentioning
confidence: 99%